Synergy Valuation of PT Indofood Sukses Makmur In Acquisition Towards PT Pepsi Cola Indobeverages - Kurniawan, Vinley Angelica; Nugroho, Anggoro Budi (Journal of Business and Management, 2015)
Abstract .This research is conducted to evaluate whether decision made by PT Indofood CBP Sukses Makmur was the right thing to do to increase firm value through acquiring PT Pepsi Cola Indobeverages. Benefit consideration gained by PT Indofood CBP Sukses Makmur for this takeover are cost saving, time saving, and all resources ready to be used by the time this acquisition was established. It was a great opportunity for PT Indofood CBP Sukses Makmur as new player in Indonesian beverage market to also earned business network chain that PT Pepsi Cola Indobeverages used to have.Synergy value for this acquisition activity calculated from information in press-release news that has become expectation for company future target has resulted increasing. In 2012 synergy value amounts in Rp3,862,409,077,069 has increased to amounts Rp4,169,928,210,000 in 2015.Moreover, feasibility study of this proposed acquisition activity also tested with NPV and IRR calculation. NPV result for this proposed acquisition activity was Rp3,832,115,754,137 which means it was economically feasible and should be accepted. IRR result was 25.72%, higher than its Cost of Capital 23.96%, which means this project is potentially feasible to increase value of the firm and should be accepted. According to Pro-Forma Income Statement, if there is no change in annual increasing of percentage of sales, company’s target to achieve net profit of Rp 5 trillion in year 2017 would not be able to be achieved. To suppress cost, PT Indofood CBP Sukses Makmur should targeting optimal sales target and efficient operating activity in which cost can be minimized.